MAKNA TOLERANSI DALAM FILM “?” (TANDA TANYA) (Analisis Framing Model Gamson dan Mondigliani) - Khoirul Huda (IAIN Ponorogo, 2018)
Abstract: Film can convey ideas in a visual form and its function is as entertainment. It influence and shape its communicants through messages and construct information through dialogue or scenes. This study examines the subject of framing employed by film creators in constructing a message through film by using the Gamson and Mondigliani model framing analysis method. It deals with the framing of messages and it analyzed the meaning of tolerance in the film